PENGARUH PRICE EARNING RATIO DAN LABA BERSIH TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Soleh Rosyad; Aan Nurhadi (The Asia Pacific Journal Of Management Studies, 2020)
The rise and fall of stock prices in the capital market is an interesting phenomenon to discuss regarding the issue of the ups and downs of the value of the company itself. One of the fluctuations in stock prices occurs in banking companies listed on the Indonesian stock exchange (BEI). The purpose of this descriptive study is to make descriptive, systematic, factual and accurate descriptions or paintings of the facts, characteristics and relationships between the phenomena being investigated. The population in this study were all banking companies listed on the Indonesia Stock Exchange for the period 2018 as many as 43 companies. The sample used is as many as 10 companies, where the sample was taken using purposive sampling technique. Based on the results of statistical calculations and data analysis that have been described in the previous chapter, it can be concluded that, there is an effect of Price Earning Ratio on stock prices. An increase in Price Earning Ratio will affect an increase in stock prices. There is an effect of net income on share prices. An increase in net income will affect an increase in share prices. There is an effect of Price Earning Ratio and net income together on stock prices. An increase in Price Earning Ratio and net income will affect the increase in stock prices.